The Supractiaphragmatic Clamping of Ruptured Aneurysms of Abdominal Aorta - Goller, Wolfgang; Nozar, José; Fernández Perdomo, Gonzalo; Burstin, Jacobo; González Miguez, Luis (Cirugía del Uruguay, 1981)
A clinical case leads the authors to support supradiaphragmatic aortic clamping through left anterolateral thoracotomy at the leve! o'f 7th or 8th intercostal space, when faced with ruptured aneurysms of abdominal aorta; in this manner it is possible to control hemorrhage and consequent coll'apse and sudden death during abdominal approach.